Population Immunity to Diphtheria and Tetanus in the Republic of Belarus Following Long-Standing Vaccination - V. L. Kolodkina; E. O. Samoilovich; V. S. Martinov; I. N. Glinskaya; V. S. Vysotskaya (Эпидемиология и вакцинопрофилактика)
Study results of IgG to diphtheria and tetanus in 785 residents aged from 1 to 76 years old from different regions of the Republic of Belarus (in 2017) in long-term (since 1996) immunization schedule: at 3, 4, 5 and at 18 months old – DTP vaccine, at 6 years old – DT, at 11 years old – Diphtheria toxoid, at 16 years old, 26 years old and every following 10 years –Td or Diphtheria toxoid are presented. The antibody concentration was measured by Virion/Serion kits (Germany) and evaluated in accordance with the international standard: less than 0.01 IU/ml – individual is susceptible, 0.01–0.09 IU/ml – levels of antitoxin giving some degree of protection, 0.1 – < 1 IU/ml – protective level of circulating antitoxin, ≥ 1.0 IU/ml – a level of antitoxin giving long-term protection. It was shown that the proportion of immune individuals against diphtheria and tetanus (with antibodies ≥ 0.01 IU/ml) was 96.7% (CI 95.4 ÷ 97.9) and 99.5% (CI 99.0 ÷ 100,0), respectively, and was quite high in all the population age groups – from 87.7 to 100% for diphtheria and from 96.5 to 100% for tetanus. In seropositive individuals IgG were presented mainly in protective and highly protective (≥ 0.1 IU/ml) titers: for diphtheria 93.7% – in 1–14 years old; 88.7% – in 15–19 years old; 78.4% – in 20–76 years old and for tetanus 100.0% – in 1–14 years old; 100.0% – in 15–19 years old; 99.3% – in 20–76 years old. Comparison of the current and previous studies results (in 1989–1994 – during the outbreak of diphtheria, in 1998–2001 – after the mass immunization campaign, in 2004 – in the context of continuous single cases of diphtheria registration in adults) had shown that the data of 2017 demonstrated the highest population immunity level to diphtheria and to tetanus in the last 30 years of observation.